USING ADOBE FLASH MOVIE TO IMPROVE STUDENTS VOCABULARY ABILITY OF NARRATIVE TEXT TO THE EIGHT GRADERS (RETAIN, 2013)
The aims of the research is to know whether watching English flash movie can improve students’ listening skill. The study is oriented towards: 1) To find out the effectiveness of using flash movie to improve the students’ listening skill; 2) To find out the advantages of using flash movie in improving student's listening skill. In order to achieve the aim of research, the researcher used experimental quantitative method. Experimental quantitative designs are commonly employed in the evaluation of educational programs. Although experimental quantitative designs need to be used commonly, they are subject to numerous interpretation problems. In this study, the researcher took the students of SMP Negeri 1 Waru Sidoarjo as population. The samples are be forty students in the Eight grade which are divided into groups are experimental and control group. The data needed was taken from a test. The test is used to identify the students’ achievement. The test is objective test. In the term pairing items consist of 10 items. After observing the data, that is the score of pre-test and post test. The writer calculating the mark of t-value and at least gives the interpretation of the calculation. Data : The scores of pre-test and post test. Analysing Data : The writer count the value oft, The researcher used two groups as the sample, each group consists of 20 students, and the degree of freedom (df) is 19 for each group. Since the two groups were chosen as representative subjects. The total df {<Nc-l)+{Nc-l)} is 38. The t-observation is 2.674. This t-observatior greater than t-critical (2.674>1.6S). Consequently, it is quite safe to reject the null hypothesis. It means that the two groups have different scores on the post-test, and the difference is statistically significant. So, this fact support the claim that students who were taught listening by using flash movie get better scores than those were taught conventionally. The experimental teaching program" can improve the students' listening skill effectively (2.90) from trial what they got in the pre-test, while control group can improve the students" listening skill less than the experimental group (2.70). The conclusion of this research is watching to the flash movie contributes the improvement of students’ listening skill, makes English lesson live, make change from the of teacher and text book, helps the students feedback has been very positive and they are enjoying the benefit of flash movie, so listening practice becomes more effective. The researcher would like propose her suggestion that teachers should try to use flash-movie in listening lesson, because watching flash movie is one type of listening experience that is interesting. Key words: Adobe Flash Movie, Vocabulary Ability, narrative text